Verwendungsregelungen und Verwertungsverbote im Strafprozessrecht - Weil, Randi (Schriften zum Strafrecht (SR), 2021)
»Rules of Use and Prohibitions of Use in Criminal Procedural Law«: The paper examines the difference between the regulations on use regulated in the Code of Criminal Procedure and the mostly non-codified prohibitions on exploitation. It undertakes de lege ferenda to define the concepts of exploitation and use, as well as to create constitutionally required statutory regulations for powers of exploitation. At the same time, the existing utilisation regulations are being reviewed for their constitutionality within the framework of a further legislative proposal.